Association between air pollution and coronary artery calcification within six metropolitan areas in the USA (the Multi-Ethnic Study of Atherosclerosis and Air Pollution): a longitudinal cohort study. Issue 10045 (13th August 2016) - Kaufman, Joel D; Adar, Sara D; Barr, R Graham; Budoff, Matthew; Burke, Gregory L; Curl, Cynthia L; Daviglus, Martha L; Roux, Ana V Diez; Gassett, Amanda J; Jacobs, David R; Kronmal, Richard; Larson, Timothy V; et al.
Summary: Background: Long-term exposure to fine particulate matter less than 2·5 μm in diameter (PM2·5 ) and traffic-related air pollutant concentrations are associated with cardiovascular risk. The disease process underlying these associations remains uncertain. We aim to assess association between long-term exposure to ambient air pollution and progression of coronary artery calcium and common carotid artery intima-media thickness. Methods: In this prospective 10-year cohort study, we repeatedly measured coronary artery calcium by CT in 6795 participants aged 45–84 years enrolled in the Multi-Ethnic Study of Atherosclerosis and Air Pollution (MESA Air) in six metropolitan areas in the USA. Repeated scans were done for nearly all participants between 2002 and 2005, for a subset of participants between 2005 and 2007, and for half of all participants between 2010 and 2012. Common carotid artery intima-media thickness was measured by ultrasound in all participants at baseline and in 2010–12 for 3459 participants. Residence-specific spatio-temporal pollution concentration models, incorporating community-specific measurements, agency monitoring data, and geographical predictors, estimated concentrations of PM2·5 and nitrogen oxides (NOX ) between 1999 and 2012. The primary aim was to examine the association between both progression of coronary artery calcium and mean carotid artery intima-media thickness and long-term exposure to ambient air pollutant concentrations (PM2·5, NOX, and black carbon) between examinations and within the six metropolitan areas, adjusting for baseline age, sex, ethnicity, socioeconomic characteristics, cardiovascular risk factors, site, and CT scanner technology. Findings: In this population, coronary calcium increased on average by 24 Agatston units per year (SD 58), and intima-media thickness by 12 μm per year (10), before adjusting for risk factors or air pollutant exposures. Participant-specific pollutant concentrations averaged over the years 2000–10 ranged from 9·2–22·6 μg PM2·5 /m 3 and 7·2–139·2 parts per billion (ppb) NOX . For each 5 μg PM2·5 /m 3 increase, coronary calcium progressed by 4·1 Agatston units per year (95% CI 1·4–6·8) and for each 40 ppb NOX coronary calcium progressed by 4·8 Agatston units per year (0·9–8·7). Pollutant exposures were not associated with intima-media thickness change. The estimate for the effect of a 5 μg/m 3 higher long-term exposure to PM2·5 in intima-media thickness was −0·9 μm per year (95% CI −3·0 to 1·3). For 40 ppb higher NOX, the estimate was 0·2 μm per year (−1·9 to 2·4). Interpretation: Increased concentrations of PM2·5 and traffic-related air pollution within metropolitan areas, in ranges commonly encountered worldwide, are associated with progression in coronary calcification, consistent with acceleration of atherosclerosis. This study supports the case for global efforts of pollution reduction in prevention of cardiovascular diseases. Funding: US Environmental Protection Agency and US National Institutes of Health.